Knowledge assets for internationalization strategy proposal - Maria Orero-Blat; Daniel Palacios Marqués; Dolores Garzón (Journal of Innovation & Knowledge (JIK), 2021)
Lack of trust, lack of references and the confidential nature of cybersecurity projects make internationalization in companies from the cybersecurity sector a great challenge. The development of lean methodologies over recent years has presented a method to reduce time and effort, measure performance in each step and pivot when it is necessary to apply a process to a different field. Considering that internationalization resembles entrepreneurship, because of uncertainty and risk in a new market where the value proposition should be validated, the Lean Start-up philosophy will serve as a theoretical framework in which to operate. The study of international challenges of cybersecurity companies and elaboration of an 'eight-step' internationalization mechanism based on Lean Start-up methodology will imply a cost-effective solution for cybersecurity enterprises that want to achieve profitability and higher return on investment in internationalization.
Keywords: M160; O31; 650; Internationalization; Innovation; Cybersecurity; Lean start-up